Efisiensi Faktor Produksi Pupuk pada Tanaman Cabai Rawit di Kecamatan Lambuya Kabupaten Konawe - Endang Sumiratin (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the efficiency of the use of fertilizer production factors in cayenne pepper plants in Lambuya Village, Lambuya District, Konawe Regency. This research was carried out in Lambuya Village, Lambuya District, Konawe Regency. Sampling uses the census method, which is to take a total sample of 30 people. The data analysis method used is economic efficiency. Based on the results of the calculation of the use of inefficient fertilizer production factors for cayenne pepper farming in Lambuya Village, Lambuya District, Konawe Regency. This is shown by an efficiency value that is not equal to one (NPMx ≠ 1), namely; the efficiency value of SP 36 is 0.70, the efficiency value of NPK Ponska is 0.87, the efficiency value of NPK Mutiara is 0.66 and the efficiency value of liquid organic fertilizer is 2.07. This means that the use of fertilizer production factors in farming is still very wasteful and inappropriate.